SON PREFERENCE AND DAUGHTER NEGLECT: GENDER DISCRIMINATION IN HARYANA - Devi, Seema (International Journal of Research -GRANTHAALAYAH, 2016)
While common people prick-up ears the name “Haryana”, it pleasure them resembling being that is knit together to flowers, blossom, greenery; on friendly terms dwelling to live and masses are pleasant, conducive nevertheless the nuts and bolts is disparate. The blush of land is “Red” and people are murders. Their including finger dukes are “Red” with “Blood” of female feticide. Haryana is solitary economically well-heeled while it move towards societal buildup, it is lifeless turned around on the point of cast back to intrinsic nethermost 914 girls for 1000 boys in the age mess of 0-6 years on the point of census. The indicated remarkably twisted infant femininity proportion is the gigantic curse for growing state alike Haryana. Regularly turn thumbs down masculinity rate teem with pretended many-a-moon dangerous segment along gender-friendly districts facing down streams. The sound mind of this evil is mightily grounded in culture, social norms, family values, religion etc. This paper examines the dominant reasons for son preference and daughter neglect in Haryana, its implications on society and to give suggestion to overcome the situation.